PENGARUH LATIHAN SHUTLLE RUN TERHADAP KELINCAHAN ATLET KYORUKI TAEKWONDO WINNER CLUB PEKANBARU - Sari, Endang Purnama; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrac: Pursuant to observation which is writer do conduct at the time of Taekwondo club winner kyoruki atlet of Pekanbaru in following various championship and in practice., most from them only awaiting attack of just opponent while practice moment only flange at just technique, but the condition of its physical of him at mobility still less nimble and opponent still can do conduct attack so that they cannot get poin number and go to the wall moment contest. This research aim to to know influence of practice of Shutlle Run To Mobility of Atlet Taekwondo Winner Club kyoruki of Pekanbaru. Form this research is research with treatment of attempt (Eksperimental), with sampel counted 6 people. Research data obtained and collected to pass through tes early and final tes before and after doing conducting practice of Shutlle Run use instrument of Shutlle Run test, with aim to to measure mobility. Afterwards, data processed with statistic, to test normalitas with test of lilifors at level of signifikan α (0.05). Hypothesis the raised is the existence of influence of practice of Shutlle Run to mobility. Pursuant to analysis test t yield Thitung equal to 110 and Ttabel 1,943, meaning Thitung > Ttabel. Pursuant to statistical analysis, there are mean of pree-test equal to 13.92 and mean of post-test equal to 12.94, hence the data normal. Thereby, there are Influence of practice of Shutlle Run To Mobility of Atlet Taekwondo Winner Club kyoruki of Pekanbaru.Keywords : Shutlle run, mobility